Investigating the Dainotti Relation in Gamma-Ray Bursts through Multipolar Electromagnetic Radiation - Emre S. Yorgancioglu; Daban Mohammed Saeed; Rahim Moradi; Yu Wang (The Astrophysical Journal)
The Dainotti relation empirically connects the isotropic plateau luminosity ( L _X ) in gamma-ray bursts (GRBs) and X-ray afterglows to the rest-frame time at which the plateau ends ( ${T}_{a}^{* }$ ), enabling both the standardization of GRBs and their use as cosmological probes. However, the precise physical mechanisms underlying this correlation remain an active area of research. Although magnetars, highly magnetized neutron stars, have been proposed as central engines powering GRB afterglows, traditional dipole spin-down radiation models fail to account for the full diversity of observed behaviors. This limitation necessitates a more comprehensive framework. We propose that multipolar magnetic field emissions from magnetars offer a plausible explanation for the Dainotti relation. Unlike simple dipole fields, higher-order multipolar configurations enable more complex energy dissipation processes. The coexistence of multiple components can plausibly explain the range of afterglow decay indices found from a sample of 238 GRBs with plateau features from the Swift-X-Ray Telescope database up to the end of 2024 December, the majority of which deviate from the dipolar prediction of α = −2, and more crucially, the spin-down physics yields a link between L _X and ${T}_{a}^{* }$ in a way that preserves the Dainotti correlation with a slope of b = −1, independent of the specific multipole order. Moreover, we find that the inclusion of higher-order multipoles can explain the range of plateau energies found in the Dainotti relations. Thus, a unified picture emerges in which multipolar fields are able to reproduce both the slope and the normalization of the correlation.